Gardner. Safe for Democracy - The Anglo American Response to Revolution, 1913-1923 - Rines, Lawrence (Teaching History: A Journal of Methods, 1991)
In my reading of the history of American diplomacy by such authors as John H. Latane, Samuel Flagg Bemis, Robert H. Ferrell, and others, I have observed that there has been a reluctance on the part of American Chief Executives to dramatically alter the foreign policy of their predecessors. Perhaps this is what has given American foreign policy the appearance of continuity.